Top Leaders Attributes in Malaysian Higher Education Institutions: Effect on University Innovation - Daud, Mafuzah Mohamad Salina; Harun, Mohd Zainal Munshid (International Journal for Innovation Education and Research, 2014)
Transforming Malaysian Higher Education Institutions to an exceptional level has become one of the main challenges in pursuing strategic vision and the ability to strengthen our Higher Education Institutions (HEIs) that could become a medium to the country economic development as well as facing global intense competition. Specifically, the role of HEIs leader is needed to transform their institution to a new paradigm. Thus HEIs leader have to furnish and equip themselves with a high leadership attributes. The main objective of this study is to investigate top leader attributes in Malaysian HEIs and it effect toward university innovation. The questionnaires were distributed to managers from various faculties and departments’ of public HEIs in Klang Valley. The findings shows, leading changes attributes of leaders is the most significantly related and asserted as the most difficult leadership challenges faced by the leader in enhancing and encouraging the spirit of innovation in HEIs.